2017
DOI: 10.1111/1471-0528.14703
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density and fractures after surgical menopause: systematic review and meta‐analysis

Abstract: Background Oophorectomy is recommended for women at increased risk for ovarian cancer. When performed at premenopausal age oophorectomy induces acute surgical menopause, with unwanted consequences. Objective To investigate bone mineral density (BMD) and fracture prevalence after surgical menopause. Search strategy A literature search of PubMed, EMBASE and Cochrane library was performed with no date restriction. Date of last search was March 1st, 2016. Selection criteria Primary studies reporting on BMD, T‐scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Calcium is one of the most important minerals that prevents osteoporosis. In postmenopausal women, a decrease in estrogen secretion accelerates bone loss and increases the risk of osteoporosis [36], and a decrease in postmenopausal BMD was observed immediately after menopause and decreased exponentially with the lapse of time, due to the continuous decrease in bone mass after menopause [37]. However, BMD only explains a portion of the bone mechanical strength variance since age-related declines in bone strength are disproportionately steeper than decreases in BMD [38].…”
Section: Discussionmentioning
confidence: 99%
“…Calcium is one of the most important minerals that prevents osteoporosis. In postmenopausal women, a decrease in estrogen secretion accelerates bone loss and increases the risk of osteoporosis [36], and a decrease in postmenopausal BMD was observed immediately after menopause and decreased exponentially with the lapse of time, due to the continuous decrease in bone mass after menopause [37]. However, BMD only explains a portion of the bone mechanical strength variance since age-related declines in bone strength are disproportionately steeper than decreases in BMD [38].…”
Section: Discussionmentioning
confidence: 99%
“…In one study, the mean BMD values were significantly lower in the surgical menopause group compared with the natural menopause group. [ 8 ] In a meta- analysis of Fakkert et al,[ 9 ] no difference was found between these two groups. In a study investigating the effect of age and menopause type on BMD, the values of patients with surgical menopause and natural menopause were shown to vary in different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis, including studies using DXA, reported significantly lower BMD in women with surgical menopause than premenopausal age-matched controls; however, there was no evidence for an additional effect of surgical menopause on BMD and fractures compared with natural menopause. 97 Interestingly, an older study employing QCT detected an increased rate of bone loss following oophorectomy. 98…”
Section: Poi After Oophorectomymentioning
confidence: 99%